Model‐informed drug development of voxelotor in sickle cell disease: Exposure‐response analysis to support dosing and confirm mechanism of action. (21st April 2022) - Green, Michelle L.; Savic, Radojka M.; Tonda, Margaret; Jorga, Karin; Washington, Carla B.
Abstract: Sickle cell disease (SCD) is characterized by the production of sickle hemoglobin (HbS), which when deoxygenated, polymerizes leading to red blood cell damage and hemolytic anemia, a defining feature of SCD. Voxelotor (Oxbryta) is a small molecule inhibitor of HbS polymerization that disrupts the polymerization mechanism by binding HbS to increase HbS oxygen affinity. Voxelotor is approved in the United States for the treatment of SCD in patients greater than or equal to 12 years of age at a 1500 mg once‐daily (q.d.) dose. These exposure‐response analyses aimed to evaluate the relationships between voxelotor whole blood concentration and change from baseline (CFB) in clinical measures of anemia and hemolysis and between voxelotor whole blood and plasma concentrations and the incidence of selected safety end points to confirm the voxelotor mechanism of action and to support the clinical dose recommendation. In patients treated with voxelotor up to 72 weeks, CFB hemoglobin (Hb) increased linearly ( p < 0.001) with increasing voxelotor concentration and percent Hb occupancy and increases in CFB Hb corresponded to improvements in measures of hemolysis. The target 1 g/dl increase in CFB Hb was achieved with 1500 mg voxelotor q.d. Significant relationships were observed between voxelotor exposures and grade greater than or equal to 1 increased alanine aminotransferase and decreased white blood cell count; however, most events were grade 1. No clinically important covariate effects on voxelotor efficacy or safety were observed. Overall, these analyses support 1500 mg q.d. as the therapeutic dose for voxelotor in adults and adolescents.